The partial clinical remission phase of type 1 diabetes: early-onset dyslipidemia, long-term complications, and disease-modifying therapies - Nwosu, Benjamin Udoka (Frontiers in Endocrinology, 2025)
No therapy confers complete β-cell protection at any of the 3 stages of type 1 diabetes (T1D). Disease-modifying therapies in type 1 diabetes aim to prolong the preclinical (stages I and II) and the post-diagnostic partial clinical remission (PR) phases of T1D to reduce its short- and long-term complications. These therapies are focused on mitigating β-cell apoptosis by reducing autoimmune attacks on surviving β-cells through several pathways; as well as improving β-cell function to enable the production of functional endogenous insulin and C-peptide through the reduction of proinsulin to C-peptide ratios and other measures. These therapies target the 3 stages of T1D as monotherapy or combination therapy. Stage I of T1D is marked by the presence of at least one diabetes-associated autoantibody in an individual with normoglycemia; stage II is marked by the presence of diabetes-associated autoantibodies and dysglycemia; stage III is marked by the clinical diagnosis of T1D in an individual with antibodies, hyperglycemia, and symptoms. Conventional thinking suggests that the long-term complications of diabetes are principally rooted in early-stage hyperglycemia at the time of diagnosis of the disease, i.e., stage III of T1D. However, this theory of hyperglycemic memory is limited as it does not address the dichotomy in lipid-based atherosclerotic cardiovascular disease (ASCVD) risk in those with T1D. Given the current limitations to developing disease-modifying therapies in T1D because of the limited impact of current agents on β-cell preservation, we introduce the theory of hyperlipidemic memory of type 1 diabetes. This theory was developed by the author in 2022 using the same population as in this article to address the shortcomings of the theory of hyperglycemic memory and explain that the dichotomy in ASCVD risk is based on PR history. In this Review, the theory presents new pathways for disease-modifying therapies in T1D that focus on preventing early-phase dyslipidemia. It is hoped that including this theoretical framework in designing disease-modifying therapies in T1D will help move the field forward. This new theory supports the hypothesis that PR is an imprimatur rather than a process. It hypothesizes that pre-diagnostic interventions, at stages I or II of T1D, to ensure the occurrence of PR may be more effective in the long term than post-diagnostic interventions, at stage III, to prolong PR. This paradigm shift in approach to disease-modifying therapy in T1D is discussed in this review.